(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article presents the results of comparative studies of the intensity of burnout syndrome in the group of managers. The Polish version of the AVEM Questionnaire for Behavior and Experience (Arbeitsbezogenes Verhaltens- und Erlebensmuster, Schaarschmidt, Fischer, 1997) in the Polish adapted version (Rongi´nska, Gaida, 2012) was used in the research. Particular attention was paid to overcoming behavior in a situation of failure, and refusal to work is seen as a leading condition for the rapid development of symptoms of professional burnout. The main components of the syndrome were selected, especially the lack of ability to cope with failure as an important reason for the rapid development of symptoms. The possibilities of preventing burnout syndrome focused on strengthening the ability to cope with failure mainly for people striving for perfection are presented.